Graphical interface for a life event management system - Silva, David Moisés Pacheco de Araújo e (2019)
The Life-Event Service (LES) provision model has the objective of providing services to citizens related to specific episodes of their daily lives that may involve several Public Administration (PA) organisms. These services have traditionally been implemented based on direct communication between organisms of the Public Administration and that might be questionable from a citizen’s privacy standpoint. The Citizen-side HAndling of Public Administration e-Services (CHAPAS) model of LES provision was proposed with the objective of discouraging direct communication between the institutions involved in a LES for obtaining the required personal information from the citizen, put the citizen in control of the dissemination of his personal information through the several institutions and promote the minimization of the information that a citizen has to supply to an institution for requesting a service that he is in the need of. To achieve this, the model requires the use of an application, Chappie, that is responsible for fulfilling the requirements for each of the services involved in the process and assist the citizen to obtain it. This application, however, had an extremely rudimentary User Interface that was in the need for several improvements. It is in this context that this work arises, with the goal of endowing Chappie with a modern User Interface capable of handling the complexity that is inherent to the integration of several services, possibly provided by different PA organisms. To achieve this, prototypes were sketched and usability studies on those were conducted in order to understand the more suitable user interaction method. The end result of this work is an application made with web technologies that can be run in personal computers and tablets that, through the use of a traditional wizard view, assists a citizen in the required steps for obtaining a service using the CHAPAS model.